Integrated Analysis of circRNA-miRNA-mRNA ceRNA Network in Cardiac Hypertrophy - Chen, Yang-Hao; Zhong, Ling-Feng; Hong, Xia; Zhu, Qian-Li; Wang, Song-Jie; Han, Ji-Bo; Huang, Wei-Jian; Ye, Bo-Zhi (Frontiers in Genetics, 2022)
Cardiac hypertrophy is an adaptive response of the heart to adapt to the changing hemodynamic demands of the body under the condition of long-term increase of preload or afterload. In recent years, more and more studies have shown that the potential relationship between myocardial hypertrophy and abnormal expression of non-coding RNAs. Circular RNA(circRNA), as one kind of the non-coding RNAs, plays a crucial role in cardiac hypertrophy. However, there are few studies that systematically and comprehensively analyze circRNA related competing endogenous RNAs (ceRNA) regulatory networks associated with cardiac hypertrophy. Therefore, we predicted and screened the differentially expressed mRNAs and miRNAs in the public database according to the online prediction website, and finally obtained circRNAs related to cardiac hypertrophy, and based on this, established circRNAs-related ceRNA regulatory network. This study is the first to establish a circRNA mediated ceRNA regulatory network associated with myocardial hypertrophy. In order to verify the results of our analysis, we used PCR to verify the differentially expressed mRNAs and miRNAs in animal myocardial hypertrophy model samples. Our findings suggest that 3 mRNAs (Col12a1, Thbs1, Tgfbr3), 4 miRNAs (miR-20a, miR-27b-3p, miR-342-3p, miR-378a-3p) and related 4 circRNAs(circ_0002702, circ_0110609, circ_0013751, circ_0047959) may play a key role in cardiac hypertrophy.